Therapeutic effect of atorvastatin on kidney functions and urinary excretion of Glimepiride in healthy adult human male subjects - Sana, Tayyaba; Aslam, Bilal; Aslam, Nosheen; Ashraf, Muhammad Mudassar; Ashraf, Asma; Malik, Tahir Aqeel; Niazi, Sammia Gul; Tahir, Imtiaz Mahmood; RiazurRehman, Muhammad; Ahmed, Hamad (Pakistan journal of pharmaceutical sciences, 2016)
Glimepiride and atorvastatin in combination are commonly employed for treating the hyperglycemia and dyslipidemia, respectively, in patients of type 2 diabetes. The present study was designed to find out the influence of atorvastatin on urinary excretion and renal clearance of Glimepiride in healthy adult male volunteers. In each experimental subject, Glimepiride 2mg was given orally after an overnight fasting. Samples of blood and urine were taken at different specific time intervals. After a washout period of ten days, Glimepiride 2mg was co-administered with atorvastatin 20mg orally. Post-medication, blood and urine samples were collected following the same sampling schedule as for Glimepiride alone. The samples were analyzed for Glimepiride and creatinine concentration by HPLC-UV and Spectrophotometer, respectively. Mean (±SE) values for blood pH 7.445±0.05 and 7.382±0.05, urine pH 4.972±0.08 and 5.08±0.10, diuresis 0.0207±0.00 and 0.0237±0.00ml/min/kg, endogenous creatinine in plasma 9.048±0.33 and 8.613±0.024µg/ml, endogenous creatinine in urine 512.34±18.20 and 556.72±4.60µg/ml, Glimepiride plasma concentration 0.16069±0.00 and 0.3227±0.01µg/ml, Glimepiride urine concentration 1.5994±0.03 and 0.8665±0.04µg/ml, renal clearance of creatinine 1.224±0.09 and 1.550±0.09ml/min/kg, renal clearance of Glimepiride 0.2064±0.01 and 0.0641±0.00ml/min/kg and clearance ratio 0.1791±0.01 and 0.0414±0.00 were observed for Glimepiride alone and its concurrent administration with atorvastatin, respectively. Atorvastatin decreased the urinary excretion and renal clearance of Glimepiride due to which chances of hypoglycemia provokes and renal handling of Glimepiride involves back diffusion besides glomerular filtration and no influence of atorvastatin was seen on these mechanisms.